Fundamentals of satellite remote sensing : an environmental approach - Chuvieco, Emilio (Boca Raton : CRC Press, 2020)
'This third edition covers the most recent advances incorporated since the publication of the previous book, relating to the acquisition and interpretation of remotely-sensed data. It includes updated EO missions, such as the third generations of geostationary meteorological satellites, the new polar orbiting platforms (Suomi), the ESA Sentinels program, and high-resolution commercial systems. Low-altitude sensing systems and improved coverage of digital techniques used to extract environmental information from remote sensing will be included as well; particularly, new machine learning classification techniques. Extended coverage of radar and LIDAR processing methods will also be included'--
Includes bibliographical references and index.
Keywords: Remote sensing; Remote sensing -- Environmental aspects; Environmental monitoring -- Remote sensing; Global environmental change -- Remote sensing